Biokinetics and dosimetric studies about 99mTc(V)-DMSA distribution. - Correia, M. B. L.; Magnata, S. S. L. P.; Silva, I. M. S.; Catanho, M. T. J. A.; Lima, F. F. (Cellular and Molecular Biology, 2010)
Research for radiodiagnostic agents should considerate biological critical parameters which will give own contribution on the absorbed dose. The dimercaptosuccinic acid (DMSA) labeled with 99mTc(V) is a radiopharmaceutical which has well established role in medullar thyroid carcinoma and has been proposed in evaluation of bone metastasis. This work studied the biokinetics and dosimetry of 99mTc(V)-DMSA by animal model. The 99mTc(V)-DMSA was prepared from a (III)DMSA kit alkalized. Mice (n=5) received 99mTc(V)DMSA i.v., they were sacrificed (30 min, 1h, 5h and 12h), the organs excised and the activities measured by a gamma counter. The results were evaluated based on %activity/g and the absorbed dose was estimated (MIRDOSE 3.0 program) by extrapolation of data from animal to human scale. The results showed the majority of organs reached the top uptake at 30 min, the greatest kidney uptake was (4.81 ± 1.38)% activity/g, while the bone presented its highest uptake at 1h (5.49 ± 0.47)% activity/g, after 1h all the organs had activity exponential decrease. The biokinetic profile of 99mTc(V)-DMSA was well established, allowing quantifying of residence time, and the radiation dose estimates were made for this agent. About the absorbed dose, the preliminary results showed higher value to bone, being the soft tissue dose relatively low.